Benefits and confidence in the interest of e-banking - Ahmad Firman; Laode Amijaya Kamaluddin (Jurnal Economic Resource, 2021)
Researchers want to find benefits and trust in the interest in using e-banking. The population in this study were all customers of Bank Sulselbar Makassar Main Branch. The sample technique used accidental sampling with a total sample of 100 respondents. Data were collected through a questionnaire which was distributed directly to the sample. Data analysis using multiple linear regression approach. The results of this study found that the benefits and beliefs have an effect on the interest in using e-banking.